Induced structural changes of humic acid by exposure of polystyrene microplastics: A spectroscopic insight - Chen, Wei; Ouyang, Zhen-Yu; Qian, Chen; Yu, Han-Qing (Environmental pollution (1987), 2018)
The occurrence of microplastics (MPs) as emerging contaminants in the environment may cause changes in water or sediment characteristics, and further affect their biogeochemical cycles. Thus, insights into the interactions between dissolved organic matter (DOM) and MPs are essential for the assessment of environmental impacts of MPs in ecosystems. Integrating spectroscopic methods with chemometric analyses, this work explored the chemical and microstructural changes of DOM-MP complex to reveal the mechanism of DOM-MP interaction at a molecular level. MPs were found to interact with the aromatic structure of DOM via π-π conjugation, then be entrapped in the DOM polymers by the carboxyl groups and C=O bonds, constituting a highly conjugated co-polymer with increased electron density. This induced the fluorescence intensity increase in DOM. The interaction affinity of DOM-MP was highly dependent on the MP size and solution pH. This work offers a new insight into the impact of MP discharge on environment and may provide an analytical framework for evaluating MP hetero-aggregation and the roles of MPs in the transportation of other contaminants. Furthermore, the integrated methods used in this work exhibit potential applications in exploring the fragmentation processes of MPs and formation of secondary MPs under natural conditions. [Display omitted] •DOM is adhered onto MPs via π-π conjugation, carboxyl groups and C=O bonds.•MP-DOM constitutes a conjugated co-polymer with an elevated electron density.•Interaction between DOM and MP depends on MP size and solution pH.•The approach has a great potential in elucidating plastics fragmentation and secondary MPs formation. The interaction mechanism between humic acid and polystyrene microplastics is explored and new insights into the impact of MP discharge on environment are provided.